Journalistic Ethics in the Age of Artificial Intelligence: Towards an Update of Deontological Codes in the Ibero-American Context - Ingrid Viviana Estrella Tutivén; Cristina Garde Cano (Comunicação e Sociedade)
This article critically reviews and updates the principles of deontological codes of communication in Ibero-American Community, aiming to adapt journalistic ethics to the new challenges posed by the advent of artificial intelligence (AI). As a qualitative analysis, it starts from the premise that current deontological codes do not include updated guidelines for the integration of AI into journalistic work. Therefore, the objective is to reformulate some of the main ethical principles and propose structural conditions that could be incorporated into the regulations governing media professionals. To achieve this, a detailed analysis of various deontological codes was conducted alongside in-depth interviews with three types of professionals: journalists, academics, and expert consultants. Some interviewees also work as fact-checkers. The interview responses were coded and analysed according to the guidelines of the constant comparative method (Wimmer & Dominick, 2013) using the ATLAS.ti platform. The results provided sufficient input to update several principles (transparency, human judgement, bias control, verification and cross-checking, avoidance of rights violations, accountability, and citizen participation), as well as to identify four structural conditions for the ethical practice of journalism in the algorithmic age (regulation for a new social pact, awareness of the impact of disinformation, media literacy, and immutable journalistic ethics; Alsius, 2011). The study concluded that the use of AI in journalistic activities requires an adaptation of existing norms to ensure and recover the quality of information and the trust of audiences. Additionally, it highlights the need for balanced regulation that does not allow media abuses through AI while also respecting press freedom.